2022
DOI: 10.3390/polym14061214
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Release Kinetics Study of Active Packaging Films Based on Modified Starch and Red Cabbage Anthocyanin Extract

Abstract: Active packaging films were prepared by adding red cabbage anthocyanin extract (RCAE) into acetylated distarch phosphate (ADSP). This paper investigated the influence of the interaction relationship between RCAE and the film matrix on the structure, barrier, antioxidant and release properties of active films. Sixteen principal compounds in RCAE were identified as anthocyanins based on mass spectroscopic analysis. Micromorphological observations indicated that the RCAE distribution uniformity in the films decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 66 publications
3
9
0
Order By: Relevance
“…The opacity is known as a positive aspect of packaging film to limit ultraviolet light transmission and protect food from adverse changes and lipid oxidation (Jiang et al, 2020 ). Cheng et al ( 2022 ) observed an increase in starch film opacity from 0.39 to 1.34 after the addition of 40% RCA. Kurek et al ( 2018 ) found that Δ E and opacity of chitosan film variably increased after the addition of blueberry and blackberry anthocyanin extracts.…”
Section: Resultsmentioning
confidence: 99%
“…The opacity is known as a positive aspect of packaging film to limit ultraviolet light transmission and protect food from adverse changes and lipid oxidation (Jiang et al, 2020 ). Cheng et al ( 2022 ) observed an increase in starch film opacity from 0.39 to 1.34 after the addition of 40% RCA. Kurek et al ( 2018 ) found that Δ E and opacity of chitosan film variably increased after the addition of blueberry and blackberry anthocyanin extracts.…”
Section: Resultsmentioning
confidence: 99%
“…Similar observations of the release behavior of encapsulated red cabbage anthocyanin extract from polymer films of modified starch were shown in ref. [ 35 ]. Therefore, a solution with an ethanol concentration of 77% was selected, which provides the optimal rate of the process.…”
Section: Methodsmentioning
confidence: 99%
“…The use of starch as a PGPB carrier is still little reported in the literature, although in recent decades its use for the encapsulation of bioactive compounds has been extensively discussed and studied [ 105 ], such as particles to encapsulate curcumin for pharmaceutical applications [ 111 , 112 ], as films to encapsulate antioxidants for food packaging [ 113 , 114 ], and as films to enhance the stability of phenolic compounds to be used in food technology [ 115 , 116 ].…”
Section: Biopolymeric Matrices As Carriers For Pgpbmentioning
confidence: 99%